1994
DOI: 10.1016/0169-5983(94)90033-7
|View full text |Cite
|
Sign up to set email alerts
|

Analytical prediction of the reflected-diffracted shock wave shape in the interaction of a regular reflection with an expansive corner

Abstract: The reflected-diffracted shock wave which develops when a regular reflection interacts with an expansive corner was investigated analytically by means of the shock dynamics theory. The results were found to agree with the linearized analytical results of Srivastava and Chopra (1970) and the experimental results of Srivastava and Deschambault (1984).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Using the continuum hypothesis, authors of the study [9] analyzed effects of the distributions of the flow temperature and velocity, as well as the size of the transition region, on the transformation of compression waves into shock waves. It was shown that a compression wave can turn into a shock wave when the perturbation velocities are sufficiently high.…”
Section: Introductionmentioning
confidence: 99%
“…Using the continuum hypothesis, authors of the study [9] analyzed effects of the distributions of the flow temperature and velocity, as well as the size of the transition region, on the transformation of compression waves into shock waves. It was shown that a compression wave can turn into a shock wave when the perturbation velocities are sufficiently high.…”
Section: Introductionmentioning
confidence: 99%
“…An incident shock Mach number of 1.45 is the boundary of the formation of the typical lambda shock structure on the shear layer since for this speed the flow becomes locally supersonic in the vicinity of the corner [1]. Analytical investigations have developed mathematical models to describe the shape of the various shock waves and the point of intersection between the incident wave and the reflected wave [5][6][7][8][9][10][11][12]. An interesting experiment was performed by Skews [13] in order to determine the reflected expansion shock profile and the angle it forms with the surface in a multi-facetted wall, made of a series of straight segments and schematically shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%